ANALYSIS OF BUDGET IMPLEMENTATION QUALITY THROUGH BUDGET ABSORPTION INDICATORS AT BKPM IN 2023 - Andrianti, Putri Makhroja; Amrania, Gia Kardina Prima (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The effectiveness of the budget implementation of a government agency is reflected in the absorption of the budget. This study examines the budget absorption indicators of the Ministry of Investment and Downstream Industry/BKPM for the year 2023 using the performance indicators for budget implementation derived from the PER-5 PB 2022 and 2024. With low absorption at the beginning of the year and a significant increase in the last quarter, the results of the analysis reveal anomalies in the absorption pattern, which suggest a slow pattern of backloading of expenditure. Internal management, budget reallocations that undermine the stability of planning and implementation, and policy and regulatory changes, such as mid-year budget changes, are the main sources of imbalance. The quality of budget implementation can be improved to promote efficiency, effectiveness, and optimization of the use of the budget following the principle of value for money in public finances. To overcome these problems, more realistic budget planning is needed, based on historical data and real needs. In addition, regular monitoring and evaluation mechanisms need to be reinforced to ensure consistency between budgetary targets and implementation in each quarter.